PENYULUHAN DAN PELATIHAN PEMANFAATAN LIMBAH PISANG SEBAGAI BAHAN BAKU KERUPUK - Ratna Mustika Wardhani; Indah Rekyani Puspitawati (JURNAL DAYA-MAS, 2022)
Abstract– Banana fruit is a fruit that has many benefits, ranging from leaves, banana midrib, banana flowers and fruit, including banana peels, because in addition to the fruit which contains many vitamins, banana peel also has a fairly high nutritional and serotonin content. So far banana peels, which are often considered worthless, can also be used to absorb heavy metals, meaning they can purify water. From the benefits of banana peel above, banana peel can be used as a basic food ingredient. Meanwhile, on this occasion the banana peel will be used as the basic ingredient for crackers. The purpose of this activity is to increase the independence of rural community business institutions and to improve the knowledge and skills of women farming communities, especially the "Reksogati" farmer women group located in Sogaten Village, Manguharjo District, Madiun City. The method used is to socialize the benefits of banana peels and conduct training. The results of community service are that processing banana peels into crackers is very easy and saves the environment from waste and has promising business prospects. Banana peel processing can contribute to new innovations in the field of food security so that it can be further developed for future needs.